Motif Mahasiswa Memilih Ilmu Perpustakaan UIN Sunan Kalijaga Berdasarkan Analisis Rational Choice Theory Raymond Boudon - Abdurokhim, Muhamad; Zain, Labibah (IAIN Ponorogo, 2024)
Abstract: Rational choice assumes that all actions come from a calculation of profit and loss, where the decision is based on information. This study aims to determine the motives of students choosing UIN Sunan Kalijaga Library Science based on rational choice. The method used in this research is qualitative with a case study approach. Data collection was carried out by purposive sampling of representatives of the 2019-2023 generation. After the data is obtained, it is then analyzed using the Miles and Huberman model. The results of the study say that the informant's decision to make a rational choice is based on the advantages and disadvantages of choosing his choice. In the aspect of advantages based on good career prospects such as ASN, high job market, superior accreditation of study programs (A), living in Yogyakarta as a student city and cultural city, relatively cheap tuition fees, alumni have spread throughout Indonesia and courses that are relevant to the needs of the times such as information systems, web design, and information and communication technology. In the aspect of losses felt by informants based on the lack of basic knowledge of library science, public perceptions that the librarian profession is underestimated, the library science study program is not known by the public, some informants consider the UKT of the last group to be quite high, library science as the second choice and lack of interest in library science. Keywords: rational choice, library science, higher education